Regulatory T Cells in the Antibody Response to Haemophilus influenzae Type b Polysaccharide - Breukels, Mijke A. (American Society for Microbiology, 1999)
An in vitro culture system for the induction of an antipolysaccharide response was used to study the cellular interactions which determine the magnitude and nature of this B-lymphocyte response. Healthy adult volunteers were vaccinated with the Haemophilus influenzae type b polysaccharide (PRP)-tetanus toxoid (TT) conjugate vaccine. Optimal in vitro anti-PRP and anti-TT antibody responses were obtained when B cells were cultured with equal amounts of T cells. The in vitro response is antigen dependent and antigen specific. Culturing with PRP mixed with TT in the presence of T cells induces the highest number of anti-PRP antibody-secreting cells (ASC) (128.4 ×/÷ 15.9 [geometric mean ×/÷ standard deviation] immunoglobulin M [IgM] anti-PRP ASC/10(6) cells; 9.3 ×/÷ 7.6 IgG anti-PRP ASC/10(6) cells). Culturing without T cells induced no anti-PRP ASC; culturing with only PRP, in the presence of T cells, yielded low numbers of anti-PRP ASC (3.7 ×/÷ 5.2 IgM anti-PRP ASC/10(6) cells and 1.2 ×/÷ 2.2 IgG anti-PRP ASC/10(6) cells). Transwell studies showed that the requirements for the antibody response against the polysaccharide are different from those of an antiprotein response. Cytokines formed as a consequence of contact between protein-specific B and T cells were on their own not sufficient to activate TT-specific B cells (8.4 ×/÷ 1.4 anti-TT ASC/10(6) cells); direct contact between T and B cells appeared to be an absolute requirement. However, physical contact between B and T cells in one compartment of the Transwell system resulted in the release of soluble factors able to stimulate B cells in the other compartment to secrete antipolysaccharide antibodies (164 ×/÷ 1.6 anti-PRP ASC/10(6) cells).